IN VITRO INVESTIGATION OF BOVINE TUBERCULOSIS IN SULAYMANIYAH, IRAQ - Kwestan N. A.; R. R. Sulaiman; H. O. Dyary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted to detect bovine tuberculosis (TB) in Sulaymaniyah, Kurdistan Region of Iraq, using gamma interferon assay (GIA), and determine the prevalence in the governorate. The study was carried out among three groups of cattle: calves aged 6–12 months, heifers 13–24 months, and cows aged above two years. Bovine TB was detected by an indirect enzyme-linked immunosorbent assay (ELISA) using the GIA, carried out on 404 cattle within the target population (31173) from different districts around the governorate. A TB prevalence rate of 8.9% was detected. The highest prevalence rate (10.5%) was in the cattle above two years of age, and the lowest rate (2.7%) was recorded in 6–12 months old calves, while the rate was 9.5% in the 13–24 month-old cattle. The results revealed that the highest positive rate (15.2%) was in Bakrajo, and the lowest rate (3.2%) was in Chwarta. The blood samples of the infected and uninfected cattle were examined for some blood parameters such as hematocrit, total and differential leukocyte counts, and erythrocyte sedimentation rate (ESR). There was a decrease in the hematocrit and leukocyte counts and an increase in ESR in infected animals. We conclude that TB is still endemic in Sulaymaniyah, Iraq, and the GIA should be used instead of other standard tests for diagnosing bovine tuberculosis.